Analisis Kelayakan Bisnis Muka Bumi Coffe House di Bandung Timur: Pendekatan Aspek Pasar, Operasional, Manajemen, dan Finansial - Fega, Amelia; Khairi, Ahmad; Nazmi, Alfathir Hilal; Sawalni, Sawalni; Firdaus, Alvin; Aprilia, Ananda; Mubarok, Adam Rizqi (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to evaluate the business feasibility of Muka Bumi Coffee House as a café business operating in East Bandung. The analysis applies a business feasibility study approach covering market and marketing aspects, operational and technical aspects, management and human resource aspects, legal, social and environmental aspects, as well as financial aspects. The research employs a descriptive method with both quantitative and qualitative approaches, utilizing primary data obtained through interviews and direct observations, along with secondary data related to revenue, operational costs, and initial investment. The financial feasibility analysis is conducted using Break Even Point (BEP), Payback Period (PP), and Accounting Rate of Return (ARR) methods. In addition, sensitivity analysis and SWOT analysis are applied to assess the business resilience against changes in sales volume and operational costs, as well as to determine its strategic position in the competitive café industry. The findings indicate that Muka Bumi Coffee House has promising market potential with relatively stable demand, supported by effective operational management and structured business organization. From a financial perspective, the business generates consistent net profit, operates above the break-even point, and demonstrates a relatively short capital recovery period. Overall, the results suggest that Muka Bumi Coffee House is financially and operationally feasible and has sustainable development prospects within the competitive coffee shop industry.